Novel G6PC3 Mutations in Patients with Congenital Neutropenia: Case Reports and Review of the Literature - Maroufi, Seyed F.; Shaka, Zoha; Mojtabavi, Helia; Sadeghalvad, Mona; Rayzan, Elham; Sedighi, Iraj; Shahkarami, Sepideh; Najafi, Mehri; Rohlfs, Meino; Klein, Christoph; Rezaei, Nima (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Background: Severe congenital neutropenia (SCN4) caused by mutations in glucose-6- phosphatase catalytic subunit 3 (G6PC3) is characterized by recurrent infections due to severe neutropenia, may be accompanied by other extra-hematopoietic manifestations; including structural heart defects, urogenital abnormalities, prominent superficial venous markings, growth retention, and inflammatory bowel diseases with rare incidence. The homozygous or compound heterozygous mutations of G6PC3 are responsible for most cases of autosomal recessive SCN4. Herein, we present two cases of SCN4 affected by novel mutations in the G6PC3, in addition to a summarized list of variants in G6PC3 gene that are reported as pathogenic and related to the SCN4 phenotype. Case Presentation: Herein, we present two cases of SCN4; the first case was a three-months old boy with severe neutropenia and prior history of hospitalization due to umbilical separation, umbilical herniation, omphalitis, and pyelonephritis; and the second case was an eight-year-old with a history of neutropenia, recurrent and severe episodes of intractable diarrhea, refractory rectovaginal and rectoperineal fistula, congenital inguinal hernia, and ASD type 2. Whole exome sequencing was performed for both cases, which revealed two novel homozygous missense mutations in G6PC3 that were predicted to be deleterious; c.337G>A, p. Gly113Arg in the first case and c.479C>T; P. Ser160Leu in the second case. To our knowledge, both of these two mutations have not been reported in the G6PDC3 gene. Conclusion: In patients with severe neutropenia with varying extra hematopoietic syndrome, mutation of G6PC3 should be suspected after ruling out other mutations related to neutropenia. This study pointed toward novel G6PC3 mutations that should be considered in order to diagnose patients with severe congenital neutropenia.
Keywords: case report